Uno na tabi? the impact of the TV Patrol Bicol shutdown to the province of Albay during natural disasters - Dayandante, Paulo R.
Access to reliable and real-time information is vital in times of natural disasters. Yet for many parts of the Philippines, this remains a challenge today even when the role of the media is needed now more than ever. Following the disfranchisement of the ABS-CBN network in 2020, the study is premised to examine the impact of the closure of its regional stations specifically the TV Patrol Bicol on the province of Albay during natural calamities. Using an integrated framework of Media Dependency and Critical Incident theories, the research assesses how the program’s discontinuation affected residents’ access to information, trust in information, and their preparedness during strong typhoons. Through paper-based survey data and supplemental interviews, the findings reveal a significant shift in news consumption patterns among Bicolano residents with social media emerging as their primary news source. The respondents also noted that their access to information, information trust, and disaster preparedness have been compromised in some ways after the channel’s closure as calculated by weighted means, all verbally translated as “Agree”. These effects were more pronounced in remote areas compared to urbanized municipalities. Thus, the study unpacks the need for media decentralization, equitable access to credible information, and support for regional journalism especially during disasters.